Hiring and firing - Tracy, Brian (HarperCollins, 2016)
Hiring and firing are difficult to get right and potentially costly to get wrong, both for your career and for the business. Hiring & Firing is the indispensable guide you absolutely must have by your side. Business expert Brian Tracy breaks down the simple but powerful strategies you can use to both bring stronger employees on board and weed out those not up to par. By learning to implement these techniques that Tracy can testify firsthand to the effectiveness of, you will make better leadership decisions that positively effect you and the business. In Hiring & Firing, you will be able to Write appealing and accurate job descriptions, Use the law of three in interviews to find suitable candidates, Ask the right questions, Probe past performance, Listen for the questions that indicate interviewees are qualified and serious, Provide clear direction and regular feedback, De-hire gracefully, and more!. At best, hiring and firing are key to improving your team and reaching your goals. Bringing on and letting go of the wrong people wastes company time and money while also reflecting poorly upon you. At worst, it could be crucial for the business in several ways. Hiring & Firing will ensure that you make the right decisions.